Exergy approach for advancing sustainability of a biomass boiler. (2018) - Compton, Marc; Rezaie, Behnaz; Rosen, Marc A.
An exergy analysis of the district energy plant at University of Idaho, Moscow, Idaho, USA is presented. Exergy flows through the components of the steam cycle through the biomass boiler are quantified to identify major sources of exergy destruction. A mathematical model is developed to determine sources of exergy destruction using measurements taken. The largest sources of exergy destruction are the boiler and furnace at 35% and 33% of the overall exergy losses, respectively, followed by the campus heating equipment at 5.7% and pressure reducing valve (PRV) at 3.5%. Parametric studies reveal that decreasing boiler steam pressure levels to reduce exergy destruction in the PRV results in increased exergy destruction rates in the boiler. Increasing boiler steam pressure levels instead reduces exergy destruction, but has negligible effects on the overall exergy efficiency of the complete cycle. This indicates that the PRV is limiting potential improvements in the boiler exergy efficiency.